Fiscalização de contratos administrativos de serviços terceirizados: Uma análise da eficácia da Instrução Normativa nº 5, de 25 de maio de 2017, no Centro de Ciências Jurídicas e Sociais da UFCG - Silva, José Irivaldo Alves Oliveira; de Almeida, Tadeu Lourenço (Desenvolvimento em Questão, 2023)
The public administration, seeking to fulfill the mission of its purposes, often needs to enter into contracts with private individuals, who need to be monitored by representatives of the administration itself. Based on this assumption, we sought to understand whether Normative Instruction No. 5 of May 25, 2017 provided sufficient guidance for the inspection activities of administrative contracts for the provision of continued services carried out at the Center for Legal and Social Sciences of the Federal University of Campina Grande were carried out satisfactorily by servants of the most diverse positions. The general objective was to diagnose whether the publication of IN No. 5 proved to be effective, that is, whether it is sufficient to guide the duties of the supervisors of administrative contracts for the provision of continuous services of the CCJS. In turn, it brought as specific objectives to analyze the evolution and effectiveness of current legislation related to the inspection of administrative contracts for outsourced services; list the advances and suggestions, in view of the inspection of administrative contracts of outsourced services of the CCJS, of IN nº 5 and propose changes in the legislation, if necessary, to the Ministry of Economy. The methodology used was descriptive with a qualitative approach. With regard to the technical procedure, the bibliographical procedure was adopted with the application of questionnaires to CCJS outsourced service contract inspectors. The results achieved indicate that IN nº 05, alone, is not sufficient to technically support contract inspection activities, requiring other interventions by the management.